Monitoring Kamera CCTV Untuk Perangkat Mobile Dengan Menggunakan Smartphone - Fahlepi Roma Doni; Wahyudin Wahyudin; Noer Azni Septiani (JURNAL TEKNIK KOMPUTER, 2019)
With the progress of the times, technology has also developed, especially application technology that shows very rapid progress, infrastructure in information technology that can support the creation of a reliable system or application has also experienced rapid development as well. The technology is used so that we can monitor or monitor the situation and situation of different places or regions by using a CCTV monitoring application, by using this application we are as if we will be in one place in front of us, the coverage that we can monitor is not limited territory, different places, islands, countries and even different continents can monitor each other. The development of computer network technology that is different in area every day is also growing and the scope is wider, not only in one area coverage, it can even become a global (world) coverage, namely using the internet, with this internet facility, then to use devices that have connected to computer networks from different areas of the place can be affordable with CCTV monitoring applications can even reach a wide area.